Associations between Brain Alpha-Tocopherol Stereoisomer Profile and Hallmarks of Brain Aging in Centenarians - Chan, Jia Pei; Tanprasertsuk, Jirayu; Johnson, Elizabeth J.; Dey, Priyankar; Bruno, Richard S.; Johnson, Mary Ann; Poon, Leonard W.; Davey, Adam; Woodard, John L.; Kuchan, Matthew J. (Antioxidants, 2024)
Brain alpha-tocopherol (αT) concentration was previously reported to be inversely associated with neurofibrillary tangle (NFT) counts in specific brain structures from centenarians. However, the contribution of natural or synthetic αT stereoisomers to this relationship is unknown. In this study, αT stereoisomers were quantified in the temporal cortex (TC) of 47 centenarians in the Georgia Centenarian Study (age: 102.2 ± 2.5 years, BMI: 22.1 ± 3.9 kg/m2) and then correlated with amyloid plaques (diffuse and neuritic plaques; DPs, NPs) and NFTs in seven brain regions. The natural stereoisomer, RRR-αT, was the primary stereoisomer in all subjects, accounting for >50% of total αT in all but five subjects. %RRR was inversely correlated with DPs in the frontal cortex (FC) (ρ = −0.35, p = 0.032) and TC (ρ = −0.34, p = 0.038). %RSS (a synthetic αT stereoisomer) was positively correlated with DPs in the TC (ρ = 0.39, p = 0.017) and with NFTs in the FC (ρ = 0.37, p = 0.024), TC (ρ = 0.42, p = 0.009), and amygdala (ρ = 0.43, p = 0.008) after controlling for covariates. Neither RRR- nor RSS-αT were associated with premortem global cognition. Even with the narrow and normal range of BMIs, BMI was correlated with %RRR-αT (ρ = 0.34, p = 0.021) and %RSS-αT (ρ = −0.45, p = 0.002). These results providing the first characterization of TC αT stereoisomer profiles in centenarians suggest that DP and NFT counts, but not premortem global cognition, are influenced by the brain accumulation of specific αT stereoisomers. Further study is needed to confirm these findings and to determine the potential role of BMI in mediating this relationship.